Diets of Sympatric Populations of American Martens (Martes americana) and Fishers (Martes pennanti) in California - Zielinski, William J.; Duncan, Neil P. (Journal of Mammalogy, 2004)
American martens ( Martes americana ) and fishers ( M. pennanti ) occur together in mixed-conifer forests of the southern Sierra Nevada. We studied their diets in the area of sympatry by examining their feces and comparing diet diversity and overlap. Diets of both species were more diverse than previously reported in North America. Although the diet of fishers appeared to include more remains of birds, lizards, hypogeous fungi, and insects than that of martens, the rank contribution of prey items to the diets did not differ and the Pianka index of dietary overlap was high. The great diversity of diets of fishers and martens may be due to the absence or rarity of large prey (e.g., snowshoe hares [ Lepus americanus ] and porcupines [ Erethizon dorsatum ]) or to a greater diversity of available prey types in the southern Sierra Nevada compared to other study sites for Martes in North America. The high degree of overlap in diets is surprising given the body size differences between martens and fishers, previously described differences in their diets, and similar use of other niche dimensions. The similarity is probably due, in part, to the relatively large pool of diverse and available resources that are exploited by both species by using similar modes of foraging. In addition, our sample of martens was drawn from the lowest margin of their elevational range in the southern Sierra; a more comprehensive survey of the diets of martens at higher elevations may yield different results.